Firearms control as an element of criminological security in the concept of transitional justice for Ukraine - Yu. V. Orlov; A. M. Yashchenko (Law and Safety)
The article is devoted to the development of a criminological model of firearms trafficking control in the context of transitional justice for Ukraine.